AN ANALYSIS OF THE EFFECT OF GOVERNMENT EXPENDITURE ON GROSS DOMESTIC PRIVATE INVESTMENT IN NIGERIA 1975-2009 - Nasir Mukhtar Gatawa; Muhammad Zayyanu Bello (European Scientific Journal, ESJ, 2012)
The paper analyses the effect of government expenditure on gross domestic private investment in Nigeria using time series annual data for 34 years. Multiple regression and cointegration methods were used to analyse the data. Result of the analysed data revealed that the actual impact of government expenditure on private investment varies depending on the type of expenditure under consideration. The negative relationship established that the federal government recurrent expenditure crowded out or substituted for private investment in the period under study. Furthermore, the study revealed a positive effect of inflation rate on private investment. The analysis suggests that government should give more priorities to expenditures that compliment private investment rather than spending on expenditures that substitute for private investment.